MEMBANGUN INTERAKSI SOSIAL ANAK PENDIAM MELALUI KEGIATAN BERMAIN PERAN DI TK MEKAR SARI - Putri Clawson; Suliem (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
The research conducted aims to find out knowing Building Social Interaction of Quiet Children Through Play Activities. This research was conducted through qualitative research methods, and using data collection techniques of observation, interviews and documentation. The study uses qualitative analysis techniques. Based on the results of the study, the conclusions obtained from this study are: In learning the activities of playing social interaction in increasing children's social interaction is very effective, this can be seen from the results of interviews and observations, indicators There is communication between quiet children through social contact shows better results in getting to know your friends, indicators Have clear goals and objectives, regardless of whether or not the goals are the same as those predicted by the actors, social acceptance indicators, indicators There are dimensions of time (past, present, and future) that will determine the attitude of the action being going even better. The results of this study indicate that playing role can increase children's social interactions. The last data analysis concluded that it was very effective when playing role as a method in increasing social interaction of quiet children in particular and other children in general, applied to children so that a positive interaction process between children and other children appeared, so that the average observations showed that children begin to actively interact and communicate with other children.